The Analysis of The Effect of Service Quality, Relationship Satisfaction, Commitment, and Trust in Loyalty Business Partners PT. Coca Cola Amatil Indonesia - Muthia Cita Hapsari; Sari Winahjoe Siswomiharjo (Dinasti International Journal of Management Science, 2022)
The company admits that continuously competitive excellence in the global economy requires companies to interweave marketing relationships to build long-term relationships with customers and other parties, one of them is a business partner. This research has purpose to find out the effect of service quality consisting of technical services (advertising and campaign) and functional services (communication and shipping), relationship satisfaction, commitment, and trust in the loyalty of business partners in this research are retail outlets. The sampling method used is simple random sampling technique. The method of collecting primary data is using a questionnaire with 132 respondents. The analytical tool used is the SEM (Structural Equation Model) using the AMOS 22 version program. The results showed that functional service quality had an effect towards satisfaction of relationship, but the quality of technical services had no effect. Outlet owner loyalty is influenced by trust but is not influenced by satisfaction and commitment. Relationship satisfaction has a positive effect on the level of commitment and trust, and trust has a positive influence on the commitment of the outlet owner.